Is the equimolar mixture of oxygen and nitrous oxide (EMONO) associated with audiovisuals effective in reducing pain and side effects during peripheral venous access placement in children? Protocol for a single-centre randomised controlled trial from Italy - Maria Lorella Giannì; Roberta Giacchero; Stefano Maiandi; Greta Ghizzardi; Valeria Edefonti; Maura Lusignani (BMJ Open, 2023)
Introduction Nurses frequently place a peripheral venous catheter during children’s hospitalisation. Many studies suggest treatment of venipuncture-related pain. The administration of an equimolar mixture of oxygen and nitrous oxide (EMONO) is employed for pain control; however, no studies have analysed the association between EMONO and audiovisuals.The purpose of the study is to evaluate the effect of EMONO administration when combined with audiovisuals (EMONO+Audiovisual) versus EMONO alone on perceived pain, side effects and level of cooperation during peripheral venous access placement in children aged 2–5 years.Methods and analysis The first 120 eligible children admitted to the paediatric ward of the Lodi Hospital and presenting the indication for peripheral venous access will be enrolled. Sixty children will be randomly assigned to the experimental group (EMONO+Audiovisual) and 60 to the control group (EMONO alone).The Face, Legs, Activity, Cry, Consolability scale will be used to assess pain in the children aged 2-years old; pain in the children aged 3–5 years will be assessed using the Wong-Baker scale. The cooperation throughout the procedure will be measured using the Groningen Distress Rating Scale.Ethics and dissemination The Milan Area 1 Ethics Committee approved the study protocol (Experiment Registry No. 2020/ST/295). The trial results will be presented at conferences and published in peer-reviewed journals.Trial registration number NCT05435118.